Content and language integrated learning in Latin America 2008-2018: Ten years of research and practice - Banegas, Dario Luis; Poole, Paige Michael; Corrales, Kathleen A. (Studies in Second Language Learning and Teaching, 2020)
Bilingual education, usually a community’s L1 and English continues spreading geographically and across educational systems worldwide. With this expansion, the development of bilingual education approaches is under constant scrutiny. One recent approach is content and language integrated learning (CLIL). European in origin, CLIL can be viewed as an educational or language teaching approach and it refers to the teaching of curricular content and L2 in an integrated manner. This approach has received international attention, yet, how CLIL unfolds in settings outside Europe appears underrepresented in international publications. The aim of this article is to provide a critical review of CLIL in Latin America between 2008 and 2018. We surveyed 64 items (articles, book chapters, and dissertations) published in regional and international outlets: 41 empirical studies, 19 practice-oriented publications, and four reviews. It begins by summarizing the CLIL continuum with a focus on content- and language-driven CLIL and CLIL frameworks. It then provides a synthesis of empirical studies and practice-oriented publications about CLIL in different Latin American settings. The corpus is analyzed following these unifying themes: pedagogy, perceptions and beliefs, teacher education, global citizenship, and language development. From this review, it transpires that Latin American CLIL is mostly implemented and examined from a language-driven perspective in private primary, secondary and higher education. Suggestions and implications for further research and practice are included.